Optimal Stock, Harvest and Effort Level of Bangladesh Trawl Shrimp Fishery â A Nonlinear Dynamic Approach - Khan, M Shamim Uddin (Journal of Agriculture & Rural Development, 2008)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if !mso]> <![endif]–> <!–[if gte mso 10]> <![endif]–> The purpose of this paper is to develop a non-linear dynamic model for Bangladesh trawl shrimp fishery for optimal control in discrete-time frame. The model has been developed on the concept of optimal resource management based on the criterion of maximization of present values of net economic revenues. The results of the optimal steady state solutions (i.e. optimal stock, harvest and effort level) for ensuring long run sustainability of the resource through the model are presented. Results reveal that Bangladesh marine shrimp fishery is not managed and utilized optimally. Present condition of high effort level, less harvest amount and less shrimp stock indicates that the danger of depletion of the resource cannot be ruled out. Key words: Bangladesh marine shrimp fishery, optimal management, non-linear dynamic model. DOI = 10.3329/jard.v5i1.1471 J Agric Rural Dev 5(1&2), 143-149, June 2007